Pengaruh Lokasi, Variasi Produk dan Harga terhadap Keputusan Pembelian pada Pusat Oleh-Oleh Osing Deles Banyuwangi - Sasmita, Mira; Cattleyana, Dilla; Rosyidah, Elok (J-MAS (Jurnal Manajemen dan Sains), 2024)
Osing Deles Banyuwangi is an individual business engaged in the shopping center for typical Banyuwangi souvenirs. This study aims to analyze the effect of location, product variety and price on purchasing decisions at the Osing Deles Banyuwangi Gift Center, both simultaneously and partially. The population in this study were consumers who were at the Osing Deles Banyuwangi Gift Center. The sampling method used is non probability sampling, data collection using accidental sampling. Data was collected using a questionnaire with a sampling sample of 60 respondents. This type of research includes quantitative using multiple linear regression analysis techniques, the coefficient of determination, simultaneous test (F test) and partial test (t test). The results showed that the location, product variety and price variables simultaneously (F test) and partially (t test) had a positive and significant influence on purchasing decisions, with a coefficient of determination (Adjust R Square) of 0.689 or 68.9% of purchasing decisions being able to be explained by independent variables, while the remaining 31.1% is likely to be explained by other independents not included in this study.